Formalising multidisciplinary peer review: developing a haematological malignancy‐specific electronic proforma and standard operating procedure to facilitate procedural efficiency and evidence‐based clinical practice. Issue 5 (May 2017) - Trotman, Judith; Trinh, Jimmy; Kwan, Yiu Lam; Estell, Jane A.; Fletcher, Julie; Archer, Kate; Lee, Kenneth; Foo, Kerwin; Curnow, Jennifer; Bianchi, Alessandra; Wignall, Lynda; Verner, Emma; et al.
Abstract : Background: Multidisciplinary team (MDT) meetings aimed at facilitating peer review have become standard practice in oncology. However, there is scant literature on the optimal structure and conduct of such meetings. Aims: To develop a process for formal peer review of patients with haematological malignancies and to audit any resulting changes made to the management recommendations of the treating physician. Methods: A standard operating procedure (SOP) for MDT meetings was developed essentially to integrate clinical peer review with weekly pathology and radiology meetings. The centrepiece is the electronic submission of a patient‐specific proforma (Microsoft InfoPath) prior to the meeting. It serves as the template for presentation, discussion and recording of recommendations and conclusions. The final verified document is stored in the electronic patient record, and a copy is sent to the general practitioner. The proposed management plans were compared to the consensus recommendations of the meeting for the first 4 years since inception. Results: Both SOP and proforma underwent continual improvements. These provided the framework for the conduct of a robust weekly MDT meeting for peer review of the management of patients with haematological malignancies. On 20% of occasions, patient management plans were altered to optimise patient care as a direct consequence on peer review at the MDT. Conclusion: Our streamlined process, in its ultimate format, has provided a mature and efficient forum for formal peer review in a genuine multidisciplinary environment. Both initial data and informal feedback support its ongoing activity as an integral component of delivering quality patient care.